(3TPhQ GdYbhO aj PcQ GdYghOs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3CeG HYO ,aEf GdJhGQjN hPcQ GdSjQ QGMI dbdH hLdGA ddge (B,(3HYO gPG JeRjb Ke (B[ (3hEf GdJGQjN (B] (3GdeSei HGdefJXe (B,(3JWGd eY ELJgGOi ai ENJUGQg , aCKQJ Cf CLJfi ai gPG GdcJGH ef CYjGf Yjhfg s
(3GfXQ GjVG HQbe (B710 (3JGQjNs
(3fSNI KGfjIs
(3hgh eNJUQ GdefJXe ai JGQjN GdCees
(3hYdi GdfSNI Cf GdcJGH ajg ef Chd GdeNdhbGJ Edi SfI (B569 (3g` s
(3hHChdgG JeRjb s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs